PERLINDUNGAN HAK-HAK PEREMPUAN MELALUI KEPEMILIKAN HARTA WARISAN MENURUT HUKUM ISLAM - Khairuddin Hasballah; Tarmizi M. Jakfar; Mursyid Djawas (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Islam teaches equality between men and women, without any differences, except in matters of nature alone. The presence of Islam brings goodness to women who were previously oppressed by the jahiliyah culture which did not recognize their position as perfect human beings like men. This research is important to do to answer the views that have been cornering Islam, that women are being looked down on and positioned as dishonorable, but it is the opposite. This research is normative-qualitative in nature by referring to the data of the arguments of the al-Qur`an and Hadith which are then analyzed from the perspective of Islamic law. This study concludes that Islam recognizes women as social creatures just like men, so they are allowed to carry out various social activities. Women are also obliged to perform worship and obedience to Allah as is required of men. Men and women have the same and equal position with Allah, although there are differences but not biologically, for example, women conceive, give birth, and breastfeeding. But both of them can work together to build a harmonious household. Islam gives women the right to own property from their business or from other results such as inheritance. Inheritance rights for women are half the rights of men. This does not mean that the position of women is half male from their human status, but because the problem of responsibility given to men is greater than that of women. Men are burdened with the responsibility of protecting and nurturing the family, including women, both as mothers, wives, and children. For justice, Islam gives more rights to men for this great responsibility, which is not given to women. So giving the inheritance to women is part of the protection of their rights.